Palmer Amaranth Control and Sorghum Response to Tank Mixtures of Huskie - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2015)
Although Huskie treatments caused significant chlorosis, the sorghum recovered fully and chlorosis did not affect yield. All tank mixes of Huskie provided good Palmer amaranth control at all rating dates. Starane NXT provided poor Palmer amaranth control at all rating dates. All tank mixes of Huskie significantly elevated yield compared to the untreated controls or Starane NXT treatments.
Keywords: Palmer amaranth; sorghum; tank mix; Huskie; weed science; weed control; herbicide